Agricultural soil microbiomes at the climate frontier: Nutrient-mediated adaptation strategies for sustainable farming - Jianfeng Du; Qixiong Gao; Fuxin Sun; Baoyou Liu; Yang Jiao; Qili Liu (Ecotoxicology and Environmental Safety)
The equilibrium transformation of soil microbial community dynamics and succession across various temporal and spatial dimensions plays a critical role in maintaining plant adaptability. Intensive agricultural practices accelerate the succession of plant microbial communities, rendering their restoration function more vulnerable. Climate change, with its variable impacts, affects the resilience of plant microbial communities through regulatory and mediating effects. Investigating the spatiotemporal dynamics of soil microbial communities in the context of climate change offers valuable insights into developing robust and resilient microbial ecosystems. This review examines the regulatory role of soil resources in plant microbial communities, the interactive effects of climate change on soil resource regulation, and the prediction of microbial community structures through resource allocation. Additionally, it explores the mechanisms that sustain ecological resilience in plant microbial community systems, emphasizing the application of the profit-averaging law.